Útil e agradável: a Revista de Educação (1934-1937) - remodelização das práticas de ensino e divulgação da política reformista educacional do governo de João Punaro Bley no Espírito Santo - Lauff, Rafaelle Flaiman (2007)
The research has Revista de Educação (from Espírito Santo) (REES) as the object of study. This periodical was published in Vitória between 1934 and 1937. During this period, the state was under federal intervention of Captain João Punaro Bley, who took over in 1930 and commanded until 1943. The production, circulation and distribution of REES were Service of Cooperation and Cultural Extension s responsibilities, which was related to Public Teaching Department of Espírito Santo. This research will favour the editorial strategies and educational prescriptions of REES. The periodical will be analyzed under Roger Chartier s theoretical assumptions, so as to elucidate the representations that were diffused in order to constitute it. For doing this, it takes the concept of strategy postulated by Michel de Certeau as fundamental to understand the production and circulation of Revista de Educação in Espírito Santo